Ingestion of host immunoglobulin by Sarcoptes scabiei - Simson Tarigan (Jurnal Ilmu Ternak dan Veteriner, 2005)
Scabies is one of the most important diseases in human and veterinary medicine. The available control measures that rely on acaricides are unsustainable, costly and environmentally unfriendly. Vaccination which is supposedly the most attractive alternative control, is sustainable, potentially cheap and environmentally friendly. Recent development in protein biochemistry and recombinant technology have facilitated the development of anti-parasite vaccine which in the past was impossible. One prerequisite for the anti-parasite-vaccine development is that the parasite has to ingest its host immunoglobulin. This study, therefore, was designed to determine whether Sarcoptes scabiei, a non blood-feeding parasite that resides on the avascular cornified layer of the skin, ingest its host immunoglobulin. Sections of routinely processed mites and skin from a mangy goat were probed with peroxidase-conjugated-anti-goat IgG and the immune complex was visualised with diaminobenzidine solution. To determine whether the ingested IgG was still intact or had been fragmented by the proteolytic enzymes, immunoblotting analysis of SDS-PAGE- fractionated proteins extracted from washed mites was performed. Quantification of IgG was done byan Elisa using purified goat IgG as control. This study showed that IgG in the mites confined to the mite’s gut only, and only a fraction of mite population ingested the IgG. The ingested IgG, as shown by immunoblot analysis, was mostly still intact. This study indicates that development of anti-scabies vaccines is reasonable.     Key Words: Sarcoptes scabiei, Immunoglobulin